Overcoming inter-observer planning variability in target volume contouring and dose planning for high-risk neuroblastoma – a European multicenter effort of the SIOPEN radiotherapy committee. (April 2023) - Jazmati, Danny; Brualla, Lorenzo; Littooij, Annemieke S; Webber, Britta; Dieckmann, Karin; Janssens, Geert O; Simon, Thorsten; Gaze, Mark N.; Merta, Julien; Serrano, Antonio; Dietzsch, Stefan; Kramer, Paul-Heinz; et al.
Abstract: Background and purpose: To establish an international quality standard for contouring and planning for high-risk neuroblastoma within the prospective High-Risk Neuroblastoma Study 2 of SIOP-Europe-Neuroblastoma (SIOPEN HR-NBL2), which includes a randomized question on dose escalation for residual disease. Materials and methods: Data on four patients with high-risk neuroblastoma were selected and distributed to the radiotherapy committee of the HR-NBL2 study for independent contouring and planning. Differences in contouring were analyzed using apparent and kappa-corrected agreement. Plans were analyzed regarding the dose-volume histogram metrics. Results were discussed among experts and agreement was obtained. Results: Substantial agreement was found for contouring of the heart (0.64), liver (0.70), left lung (0.74), and right lung (0.74). For contouring of the gastrointestinal tract (0.54), left kidney (0.60), and right kidney (0.59) moderate agreement was obtained. For target volume delineation, agreement for preoperative tumour extent was moderate (0.42), for CTV fair (0.35) and only low (0.06) for residual tumour, respectively. The dose planning strategies appeared to be relatively homogeneous among all experts. Conclusion: Considerable variability was found for the delineation of target volumes, particularly the boost volume, whereas the contouring of the organs at risk and the planning strategy were reasonably consistent. In order to obtain reliable results from the randomized HR-NBL2 trial, standardization of target volume delineation based on adequate imaging is crucial.